Mutation load decreases with haplotype age in wild Soay sheep - Martin A. Stoffel; Susan E. Johnston; Jill G. Pilkington; Josephine M. Pemberton (Evolution Letters, 2021)
Abstract Runs of homozygosity (ROH) are pervasive in diploid genomes and expose the effects of deleterious recessive mutations, but how exactly these regions contribute to variation in fitness remains unclear. Here, we combined empirical analyses and simulations to explore the deleterious effects of ROH with varying genetic map lengths in wild Soay sheep. Using a long‐term dataset of 4879 individuals genotyped at 417K SNPs, we found that inbreeding depression increases with ROH length. A 1% genomic increase in long ROH (>12.5 cM) reduced the odds of first‐year survival by 12.4% compared to only 7.7% for medium ROH (1.56–12.5 cM), whereas short ROH (<1.56 cM) had no effect on survival. We show by forward genetic simulations that this is predicted: compared to shorter ROH, long ROH will have higher densities of deleterious alleles, with larger average effects on fitness and lower population frequencies. Taken together, our results are consistent with the idea that the mutation load decreases in older haplotypes underlying shorter ROH, where purifying selection has had more time to purge deleterious mutations. Finally, our study demonstrates that strong inbreeding depression can persist despite ongoing purging in a historically small population.